The methodology for calculation of road accident costs - Pukalskas, Saugirdas; Pečeliūnas, Robertas; Sadauskas, Vigilijus; Kilikevičienė, Kristina; Bogdevičius, Marijonas (Transport, 2015)
The presented methodology for accounting the costs caused by road accidents is based on the fact that a person who died or was injured in a traffic accident will not contribute to the economic wealfare of the country anymore or his/her contribution will reduce. Broken vehicles, damaged cargoes or defected road constructions cause huge losses to the state. A financial assessment of material losses caused by road accidents enables providing a feasibility report in respect of efficiency of newly introduced traffic safety measures. The aim of the presented methodology is an establishment of the road accident costs that would conform to the todays economic level of Lithuania. The developed methodology for accounting road accident costs will enable more precise assessment of a necessity, perspectives and priorities of investment projects in the transport system as well as an accomplishment of funding allocation tasks.First Published Online: 27 Mar 2015